Advocacy on Combating Hunger - Harris, Rahadyan Fajar; Wahyuni, Indria; Prihatiningtyas, Wilda (Faculty of Law, Universitas Negeri Semarang, 2023)
The imperative to expedite the reduction of stunting rates has emerged as a paramount policy goal, garnering unanimous support from local governments across Indonesia. Banyuwangi Regency, in its commitment to this cause, has introduced the Banyuwangi Tanggap Stunting (BTS) Program, an innovative initiative aimed at diminishing stunting prevalence. The success of this program hinges on the endorsement and proactive involvement of all village governments within Banyuwangi Regency. Crucially, the efficacy of such policies necessitates a foundation rooted in the Political Will of village governments to facilitate implementation. This study delves into the case of Kedunggebang Village, situated in the Tegaldlimo District, which has embarked on the BTS program through a collaborative, cross-sectoral approach and extensive community counseling efforts. The primary objective of this research is to elucidate the Political Will exhibited by the Kedunggebang village government in supporting the BTS initiative, while also examining the impediments encountered during its implementation. Employing qualitative descriptive methods and in-depth interviews, this research employs the Brinkerhoff Theory as an analytical framework. Notably, the study stands out as a multidisciplinary exploration, scrutinizing public health concerns through the lenses of public policy and government bureaucracy. The findings reveal a nuanced scenario where the Kedunggebang Village Government demonstrates a lower level of Political Will, yet exhibits the capacity to effectively implement the BTS program. Consequently, the study advocates for essential bureaucratic reforms, including the enactment of village regulations, the formulation of comprehensive village development plans, and the establishment of a dedicated task force to accelerate the reduction of stunting rates.